Analisis Performa Dalam Jaringan Ad-Hoc (Studi Kasus: PT. Trimitra Usaha Sejahtera) - Zidan Rafansyah; Muhajir Syamsu; Shevti Arbekti Arman (ITB Ahmad Dahlan Jakarta, 2024)
An ad-hoc network is a topology that directly connects a wireless network between end users to other end users without using other connected devices. For example, a network between a computer and another computer uses wireless transmission media. The interface used is a wireless card or wireless USB or other end user network device. The implementation of this particular topology is very convenient and very easy because it does not require much configuration, just create an adhoc network as a station on one of the computers and then configure the IP address. This research aims to see the performance produced when there is a delay, and throughput to see stable results, this method uses NDLC (Network Devlopment Life Cycle) to analyze the resulting performance with QOS (Quality Of Service) parameters for calculating results according to TIPHON (Telecommunication) standards and internet protocol hormoneization over network) 5.5% to 100% good results with this stability (data sharing and communication carried out in the office with predetermined bandwidth management so that it can be used according to the required capacity experiences quite different changes so that the resulting performance is appropriate or not too far from the standard results with 3.5% and 5.5% which is much more stable for the resulting performance.